Does Physical Fitness Correlate with IQ? A Study among Football Student-Athletes - Nurcahyo, Panuwun Joko; Kusnandar, Kusnandar; Budi, Didik Rilastiyo; Listiandi, Arfin Deri; Kurniawati, Henie; Widyaningsih, Rindha (Universitas Pendidikan Indonesia, 2021)
This study aimed to determine the relationship between the level of physical fitness with intellectual intelligence (IQ) in soccer athletes. The research method uses the correlational method. The sample in this study were 13 male soccer athletes who were members of the football Club at the college level. The sampling technique used was purposive sampling. The research instrument used to measure students' physical fitness was the Multilevel Fitness Test (MFT). Meanwhile, the measurement of intellectual intelligence (IQ) uses an IQ test with Standard Progressive Matrices (SPM) test. Data analysis used a correlation test to confirm the relationship between physical fitness and intellectual intelligence (IQ). The results showed that the male soccer athletes' average level of physical fitness (Vo2 Max) was in a good category. The intermediate IQ level is in the High Average category. The correlation test shows a linear relationship between physical fitness and intellectual intelligence (IQ). The better the physical fitness, the higher the intellectual intelligence.